Association Between Body Weight Growth and Selected Physiological Parameters in Male Japanese Quail (Coturnrix japonica) - Vatsalya, Vatsalya; Arora , Kashmiri L. (International Journal of Poultry Science, 2011)
Japanese quail is very popular research animal model. Its continued characterization for various norms is highly desirable for obtaining accurate and reliable results. This study was designed to assess various physiological parameters which are associated with body growth and development. Among various physiological parameters, blood constituents and hormones are commonly used as diagnostic tools in both physiological and pathological evaluations of humans and animals. Japanese quail hatchlings were housed in the temperature controlled brooders up to 3 weeks of age and then shifted to hanging cages in air conditioned room at 74 F under 14L:10D lighting system and free access to feed and fresh water. Starting d8, a group of birds of uniform size and weight were selected randomly and euthanized at 4-day intervals up to d52 of age. The birds were weighed and blood sampled from the brachial vein for measuring Blood Glucose (BGL), Total Plasma Proteins (PP) and Packed Cell Volume (PCV). It was found that starting d36 all the three physiological parameters altered with approaching sexual maturity (d48-52): BGL decreased (252 vrs.182 mg/dl, p<0.05), PCV% increased (43.6 vrs. 49.6%, p<0.05) and PP also increased (2.7 vrs. 3.2 gm/dl, p>0.05). Accordingly, BGL, PCV and PP values demonstrated significant potential to predict approaching sexual maturity in male Japanese quail.